THE DEVELOPMENT LKS ORIENTED CTL ON MATERIAL DIGESTIVE SYSTEM IN CLASS VIII SMP - SUCI IRAWATI, MAYA (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
LKS is used in SMP PGRI 29 Surabaya on material digestive system has never been done using practical activities and worksheets that CTL oriented.This research aims to: Analyze the results of feasibility worksheets developed CTL, to describe the students' response to LKS CTL developed. The design of this research is using the device according Kemp.The worksheet is evaluated from the results of the feasibility study, feasibility worksheets and student response. Based on the research, the result is obtained by: The results of the feasibility study worksheets at 87,33% with very decent category, Response 95.55% of students with criteria very well. Keywords: Development LKS, CTL, digestive system